Cholera toxin enhances vaccine-induced protection against Mycobacterium tuberculosis challenge in mice - Griffiths, K; Stylianou, E; Poyntz, H; Betts, G; Fletcher, H; McShane, H (Public Library of Science, 2013)
Interleukin (IL)-17 is emerging as an important cytokine in vaccine-induced protection against tuberculosis disease in animal models. Here we show that compared to parenteral delivery, BCG delivered mucosally enhances cytokine production, including interferon gamma and IL-17, in the lungs. Furthermore, we find that cholera toxin, delivered mucosally along with BCG, further enhances IL-17 production by CD4+ T cells over mucosal BCG alone both in the lungs and systemically. This boosting effect of CT is also observed using a vaccine regimen of BCG followed by the candidate vaccine MVA85A. Using a murine Mycobacterium tuberculosis (M.tb) aerosol challenge model, we demonstrate the ability of cholera toxin delivered at the time of a priming BCG vaccination to improve protection against tuberculosis disease in a manner at least partially dependent on the observed increase in IL-17. This observed increase in IL-17 in the lungs has no adverse effect on lung pathology following M.tb challenge, indicating that IL-17 can safely be boosted in murine lungs in a vaccine/M.tb challenge setting.